Indonesian Government’s Strategies on Obtaining Market Access of Wood Products in EU Countries with Forest Law Enforcement, Governance and Trade - Voluntary Partnership Agreement (FLEGT-VPA) (2007-2016) - Putri, Komang Audina Permana (Nation State: Journal of International Studies, 2020)
Forestry has played an important role in Indonesia's economic development. Forestry and related products contribute approximately 3.5 per cent to Indonesia’s GDP and contribute to the livelihoods of 15 million Indonesian people. Major importer countries of Indonesian wood products comprise to several countries including European Union (EU). However, Indonesia export on wood product activities has significant challenge on the legality of forestry and related products. Illegal logging issues in Indonesia have become Indonesia’s major historical problem around the forestry industries. This is related to the issues that most of the wood products produced by the Indonesian timber industry are derived from illegal timber so that buyers from European Union countries are forced to reject the import of these wood products. Thus, the purpose of this article is to analyze Indonesian government strategy to obtain woods market in EU. Following by the issues, Indonesia need to reform the certification system and also the policy reforms to adjust the EU standard regulation. That is why Indonesian government began to cooperate with the European Union through the FLEGT-VPA program.